Mayo Clinic infectious disease case review : with board-style questions and answers - Baddour, Larry M.; O'Horo, John C.; Enzler, Mark J.; Kashyap, Rahul (New York, NY : Oxford University Press, 2022)
'Mayo Clinic Infectious Disease Case Review' is a comprehensive collection of case studies covering a wide array of infectious diseases. This volume addresses many common illnesses that primary care clinicians and infectious diseases specialists will see during their practice. With a focus on epidemiology, the investigative study of each case addresses laboratory tools to be used and how to interpret the results.
Also issued in print: 2022.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on January 20, 2022).
Keywords: Communicable diseases -- Diagnosis; Communicable diseases -- Treatment; Communicable diseases -- Examinations, questions, etc